2022
DOI: 10.1617/s11527-021-01837-0
|View full text |Cite|
|
Sign up to set email alerts
|

Recommendation of RILEM TC 264 RAP on the evaluation of asphalt recycling agents for hot mix asphalt

Abstract: This recommendation is based on the results of an inter-laboratory study organised by the RILEM technical committee TC 264-RAP "Asphalt Pavement Recycling"—Task Group 3 (TG3) focusing on Asphalt Binder for Recycled Asphalt Mixture. The TG3 aimed to evaluate the effect of a specific family of materials known as asphalt recycling agent (ARA) on the aged binder under different configurations. Even though ageing is an irreversible phenomenon, effective ARA must have the capability to improve the flexibility of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The cylindrical specimens with a diameter of 100 mm and a height of 63.5 mm were prepared for the indirect tensile (IDT) test. Considering that the actual load acting on the pavement is constant and the deformation of the pavement grows with the growth of the constant load, the stress-controlled mode was used to perform the IDT test at 25 • C. To obtain the fatigue life of RAM, the average indirect tensile strengths of the different types of mixtures under dry conditions were first obtained from the IDT test, and then the stress ratio (0.25) for the fatigue test was determined [32,33]. Finally, the fatigue life was obtained based on the vertical permanent strain curve of the asphalt mixture, which was used to evaluate the medium-temperature fatigue performance of RAM.…”
Section: Indirect Tensile Testmentioning
confidence: 99%
“…The cylindrical specimens with a diameter of 100 mm and a height of 63.5 mm were prepared for the indirect tensile (IDT) test. Considering that the actual load acting on the pavement is constant and the deformation of the pavement grows with the growth of the constant load, the stress-controlled mode was used to perform the IDT test at 25 • C. To obtain the fatigue life of RAM, the average indirect tensile strengths of the different types of mixtures under dry conditions were first obtained from the IDT test, and then the stress ratio (0.25) for the fatigue test was determined [32,33]. Finally, the fatigue life was obtained based on the vertical permanent strain curve of the asphalt mixture, which was used to evaluate the medium-temperature fatigue performance of RAM.…”
Section: Indirect Tensile Testmentioning
confidence: 99%
“…It was found that different types of fiber can ultimately lead to an increment in moisture, fatigue, and rutting resistance performance in asphalt mixtures containing high content of RAP (Fakhri and Hosseini, 2017;Wu et al, 2020;Ziari et al, 2020Ziari et al, , 2021. In Europe, up to 50% RAP can be recognized as high RAP content (EAPA, 2022;Hugener et al, 2022). Hence, it was validated that the use of fiber could reinforce the performance properties of AC and PA mixtures, with and without RAP, at intermediate and high temperatures.…”
Section: Research Backgroundmentioning
confidence: 99%
“…The findings revealed that the fine particles within the RAP aggregates were not adequately separated from the original aggregates, resulting in decreased mixture density and increased void content [40][41][42]. Other relevant studies have demonstrated that the role of mineral particles and asphalt in RAP differs from that in conventional mixtures, leading to deviations in the expected gradation and compromising pavement compaction quality [43,44]. The RAP in the mixture can result in poorer performance if conventional design methods are applied.…”
Section: Introductionmentioning
confidence: 99%